The use of solid emulsifier in building materials based on emulsified bitumen - Savva Viktorovich Skorikov; Yulia Gennadievna Lozikova (Вестник Северо-Кавказского федерального университета, 2022)
The developed compositions and technology of preparation of materials with improved performance characteristics. This is achieved through the use of as solid emulsifiers in bitumen pastes cements the different brands of mineral powders with hydrophilic and hydrophobic surface or their mixtures.